Enhancing the Quality of Islamic Education through Appropriate Educational Financing: Enhancing the Quality of Islamic Education - Fauzi; Hamdi Abdul Karim; Nasrin Hasibuan (Global Action and Education for Society, 2026)
This study aims to explore the role of appropriate educational financing in enhancing the quality of Islamic education. Using a qualitative descriptive approach through literature review, this article examines various financing strategies implemented by Islamic educational institutions in Indonesia and their impact on institutional performance. Findings from eight different studies reveal that effective financial management—characterized by transparency, accountability, and community participation—contributes significantly to improving teacher welfare, infrastructure quality, and student achievement. Moreover, diverse funding sources such as government aid, community contributions, and productive waqf are proven to enhance financial resilience and sustainability. The discussion highlights that financial governance in Islamic education must go beyond administrative functions and be oriented toward long-term educational development based on Islamic values. The study concludes that educational financing is not merely a technical component but a strategic pillar in realizing inclusive, competitive, and high-quality Islamic education.